Human Learning: implicit and explicit - Jarvis, Peter (2015)
Building on Polanyi’s insight in The Tacit Dimension that we know more than we can tell, this paper argues that we actually experience more of reality than that of which we are conscious. Our conscious experience becomes the basis of explicit learning but that which we experience but of which we are not conscious is the basis of implicit learning and tacit knowledge.